Konflik Preferensi Negara dan Pemegang Hak Tanggungan dalam Kasus Sita Pajak di KPKNL Surabaya - Jalil, Moh Fadhel Abd; Lamonsya, Muhamad Nabil; Chivalry, Muhammad Alisra; Maulana, Puja; Najmudin, Nandang (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the conflict between the state’s right of priority over tax debts and the position of the holder of a security right in the execution of collateral, focusing on a case of tax seizure that obstructed an auction at the State Asset and Auction Service Office in Surabaya. The main issue arises from the overlapping authority between tax officials and the state auction office when collateral already encumbered with a security right is also subjected to seizure due to the debtor’s outstanding tax obligations. The purpose of this study is to explain the legal standing of each party, assess the practical handling of auctions in real cases, identify the implications of this priority conflict for legal certainty for creditors, and formulate recommendations for more harmonious regulatory arrangements. The research method used is a normative legal approach supported by empirical analysis of auction practices, including the review of documents and field observations. The findings indicate that although the holder of a security right has priority in debt repayment, the application of the state’s priority over tax obligations often delays or hinders the execution of collateral, creating legal uncertainty and financial risks for creditors. Furthermore, inconsistencies between tax regulations and security law contribute to procedural confusion in the auction process. This study concludes that regulatory reconstruction is necessary to clearly govern the relationship between the state’s priority rights and security rights to avoid authority conflicts and ensure legal protection and certainty for all parties involved.